2018
DOI: 10.1039/c7ra13344h
|View full text |Cite
|
Sign up to set email alerts
|

A study on the preparation of pitch-based high-strength columnar activated carbon and mechanism of phenol adsorption from aqueous solution

Abstract: Coal tar pitch was ground into powder and hydroformed with high pressure. After pre-oxidation, the pitch was activated by CO 2 at high temperature. The effects of different preparation conditions on the yield, pore structure and phenol adsorption capacity of activated carbon were investigated, and activated carbon prepared under suitable conditions had good adsorption performance. A pore volume of 1-10 nm is the main absorption structure according to the analysis of pore size distribution and phenol adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…It is evident that the elemental composition descending sequence is referring to O (49.08%) < C (48.13%) < K (1.74%) < Zn (0.30%) < P (0.21) < Fe (0.19%) < Ca (0.15%) < Mg (0.13%) < Na (0.06%). The current results confirm that oxygen and carbon contents constitute the majority with 97.21%, while the other components are minor as mentioned earlier [52].…”
Section: Logc E B Hj and A Hjsupporting
confidence: 90%
“…It is evident that the elemental composition descending sequence is referring to O (49.08%) < C (48.13%) < K (1.74%) < Zn (0.30%) < P (0.21) < Fe (0.19%) < Ca (0.15%) < Mg (0.13%) < Na (0.06%). The current results confirm that oxygen and carbon contents constitute the majority with 97.21%, while the other components are minor as mentioned earlier [52].…”
Section: Logc E B Hj and A Hjsupporting
confidence: 90%
“…Therefore, the Langmuir model might be the most appropriate model to describe the adsorption of phenol on FWAC. Lv et al, Kumar and Jena, and Yao et al have also found that the Langmuir model was the most suitable model to describe phenol adsorption on activated carbons.…”
Section: Resultsmentioning
confidence: 98%
“…The band at 705 cm À1 suggests the aromatic nature of the hydrocarbon. 15 The primary gel permeation chromatograph analysis of various pitch precursors is represented in Table 2. From the analysis, it is comprehended that the polydispersity of the petroleum pitch is highest and that of the mesophase is lowest.…”
Section: Resultsmentioning
confidence: 99%